MIL-100(Fe) MOF as an emerging sulfur-host cathode for ultra long-cycle Metal-Sulfur batteries - Bonilla, Álvaro (2024)
Metal–Sulfur (Li/Na–S) battery technology is considered one of the most promising energy storage systems because of its high specific capacity of 1675 mA h/g, attributed to sulfur. However, the rapid capacity degradation, mainly caused by metallic polysulfide dissolution, remains a significant challenge prior to practical applications. This work demonstrates for the first time that a Fe-based metal organic framework (MIL-100(Fe)) can remarkably stabilize the electrochemical behavior of sulfur-cathodes in Metal-S cells during prolonged cycling. The chemical and morphological properties of MIL-100(Fe) and, especially conjugated with their textural characteristics, can help immobilize lithium/sodium polysulfides within the highly microporous cathode structure. Capacity loss per cycle is 0.044 mA h after 3000 cycles at 2C in Li–S cells. This behavior is confirmed when the MOF-based cathode is studied in RT Na–S batteries, managing to stabilize the capacity with a loss of less than 0.08 % during 2000 cycles at 0.1 C-rate. The excellent performance can be attributed to the synergistic effects of the highly microporous structure of MOF-100(Fe), which provide an ideal matrix to confine polysulfides, and the presence of Fe(III) active centers that provide chemical affinities to sulfur and polysulfides. These factors contribute to the excellent cycling performance of the S@MIL-100(Fe) composite in Metal-Sulfur batteries.